Нелинейное деформирование двухслойной плоской криволинейной системы - Ободан, Н.И.; Гук, Н.А.; Козакова, Н.Л. (Проблемы машиностроения, 2017)
Изучено нелинейное поведение двухслойной криволинейной системы, нагруженной распределенной поверхностной нагрузкой и возмущением в виде силы, приложенной к нижнему слою. Задача формулируется в вариационной постановке. Произведен численный анализ нелинейного напряженно-деформированного состояния слоя в зависимости от высоты нижнего слоя, угла модели, коэффициента трения и относительной жесткости слоев. Установлены возможность и особенности потери устойчивости нижнего слоя и всей системы в целом, исследована их связь с параметрами системы. Досліджена нелінійна поведінка двошарової криволінійної системи, що знаходиться під дією розподіленого поверхневого навантаження і збурення у вигляді сили, що прикладена до нижнього шару. Задача формулюється у варіаційній постановці. Здійснений числовий аналіз нелінійного напружено-деформованого стану шарів в залежності від висоти нижнього шару, кута моделі, коефіцієнта тертя і відносної жорсткості шарів. Встановлені можливість і особливості втрати стійкості нижнього шару та усієї системи в цілому, досліджений їх зв’язок з параметрами системи. Nonlinear behavior of a two-layer curved system is investigated. The system of layers is exposed distributed load on surface and disturbances force. The force is applied to the lower layer. At the boundary where the layers are separated, in the contact zone, boundary conditions corresponding to the clutch area slipping and separation are possible. The method of solution is based on the variation formulation of the boundary value problem using characteristic functions. For the solving of the problem the finite element approximation is used. Numerical analysis of non-linear stress-strain state and stability of the upper layer depending on the height of the bottom layer, the angle model, the coefficient of friction and the relative stiffness of the layers, was produced. Analysis of the behavior of a two-layer system showed that at a certain ratio of the thickness of the layers and the values of the existing load, the deformation in the presence of slip, contact, and separation zones is possible. Moreover, the existence of this behavior depends on the system parameters and can be found in series calculations with load change from zero to the final value. Possibility and characteristics the loss of stability of the layer and the entire system have been found, their relationship with parameters of the system are investigated.